The Effect Of PP 55 Of 2022 Implementation And Taxation Socialisation On Tax Compliance Level Of MSMEs - Lasando Lumban Gaol; Vebry M Lumban Gaol (UNIVED Press, 2023)
This study aims to examine the effect of the Implementation of PP 55 of 2022 and taxation socialization on the tax compliance of MSMEs in Medan City. In this study, data were obtained from questionnaires distributed to 51 MSME respondents in Medan City. The analysis results show that the Implementation of PP 55 of 2022 and taxation socialization together have a positive and significant effect on the tax compliance of MSMEs. These results indicate that tax incentive policies such as PP Number 55 Year 2022 can help MSMEs in economic recovery post Covid-19 pandemic, while the government's intensive taxation socialization can increase taxpayer compliance to fulfill all their tax obligations. In order to improve the tax compliance of MSMEs, continuous socialization regarding tax incentive policies and the use of digital technology are needed to increase the effectiveness of tax education.